Evaluating a mobile-based short virtual course on family planning for frontline health workers in India - Farhad Ali; Gelsey Bennett; S. Vijay Paulraj; Sanjay Kumar Paswan; Vir Narayan; Adam Wills (Journal of Global Health Reports)
One of the ways to address the critical gap of trained human resources in health is to train frontline workers (FLW) on health prevention and health promotion. The FLW play an important role in community mobilization, outreach activities, and service delivery at the last mile. In rural India, the number of internet and smartphone users is rapidly increasing, presenting an opportunity to reach and virtually train FLW. The current evidence base shows progress towards creating and using mobile-based training, but significant work is needed to improve the quality of mobile-based training programs. This study showcases Project *Samvad*’s experience in creating and rolling out a virtual training course for FLW, highlighting the feasibility of virtual training at scale and the quality of engagement of the participants with the course content. The method for this descriptive study is divided into two broad categories: (i) course development, promotion, and rollout processes, and (ii) course evaluation. Both qualitative and quantitative approaches were used to collect and analyze data. We found that the overall average course completion rate was 82% (992 out of 1211 registrants). The average increase in the endline question accuracy was around 15 percentage points from the baseline. We conclude that mobile-based virtual training of FLW is feasible and program managers and policymakers should consider creating hyperlocal course content, ensure participation of partners at various stages of development and rollout of the course and use a peer-to-peer and community-led system to support the learners.